Selection of appropriate solid wood species for bending-active structures - Akyurek, Muhammed Emin; Girgin, Zehra Canan (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2023)
The general purpose of this study is to define the bendability criteria of grid shell. In particular, it is aimed to determine the suitability of woods in Turkey for grid shell with analytical methods. Theory and Methods: In this study, bending capacity of grid shells were examined according to tree type, sizing and detailing. Design radius of curvature (Rt) was defined for 20mm thick laths regarding Turkiye woods simply in terms of allowable bending strength (o -em) and elastic modulus (E). Rt values were compared with USFPL's experimental radius of curvature (Rd) to verify the relationship between design and experimental method, relationship was confirmed with very high correlation coefficient t (r=0.97). Proper woods were determined through regression analyses among Rt, E, rho, production amount and cost. Bendability and mechanical characteristics of some woods were also compared with the case studies and Europe. Finally, wood species in Turkiye were classified through the criteria of usability and ordering to the importance in the grid shell. Results: In the structures examined, the ratio of height to length of the laths is 0.23-0.30, and the ratio to span is 0.33-0.41. In terms of lightness and bendability, the material should have a thin section, straight fibers, few knots, high bending strength, low elastic modulus and low density. In terms of lightness and bendability, larch from softwoods and maple and linden from hardwoods are the most efficient examples Yet, production of maple and linden are insufficient. Generally, the cost increases as the radius of curvature decreases. Oak is relatively expensive due to its durability (Figure A). The bending ability of larch, oak and beech is higher than its European counterparts with its low elastic modulus and high bending strength. The European Spruce, on the other hand, is more qualified than its example in Turkey. Conclusion: Among all Turkish woods examined, Oak, beech and larch in Turkiye are the most suitable woods in terms of supply, mechanical properties and bendability for grid shell construction.
Keywords: Elastic structures; Timber grid shell; Turkiye woods; Material selection; Radius of curvature; DESIGN; CONSTRUCTION; Engineering